Pengaruh Internship Experience Dan Soft Skill Terhadap Kesiapan Kerja (Studi Pada Mahasiswa Manajemen Angkatan 2018 & 2019) - Sri Wahyuni; Fitri Kumalasari; Andry Stepahnie Titing (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine: (1) The influence of internship experience on the work readiness of Management students in the class of 2018 & 2019. (2) The influence of soft skills on the work readiness of Management students in the class of 2018 & 2019. Based on the results of initial observations on 40 Management students in the class of 2018 and 2019. Of those who have carried out internships, only 42% have work readiness and 58% do not have work readiness. This can be concluded that students who do not have work readiness are influenced by the lack of work readiness that half of their work experience has. So researchers conducted this research using a quantitative approach. Data collection in this research used observation, documentation and distribution of questionnaires. The population of this research is Management Students Class of 2018 & 2019, Nineteen November University, Kolaka, totaling 281 students. Meanwhile, the sample for this research was 165 students. Research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is testing the measurement model (outer model) and testing the structural model (inner model) with Smart PLS 4.0. Based on the research results, it is known that there is a positive and significant influence between the Internship Experience variable on work readiness as indicated by a P-Value of 0.001. Meanwhile, the Soft Skill variable has a positive and significant effect on work readiness as indicated by a P-Value of 0.002.